The Impact of Entrepreneurship Education, Resource Access, and Technology Adoption on Students' Interest in Entrepreneurship in Plastic Recycled Products - Mabrur, Imam; Dewi, Novi Yanti Sandra; Hidayanti, Nur Fitri (JMK (Jurnal Manajemen dan Kewirausahaan), 2025)
Plastic waste is a global environmental challenge. One potential solution is to promote entrepreneurship in plastic recycling. However, this approach remains relatively limited and requires greater attention. This research seeks to analyse the impact of entrepreneurship education, resource access, and technology adoption on student interest in entrepreneurship plastic recycled products. A quantitative methodology was utilised, involving a survey administered to 110 students from Muhammadiyah Mataram University who had engaged in entrepreneurship training. The results showed that entrepreneurship education, resource access, and technology adoption positively and significantly affect entrepreneurial interest, with contributions of 26.5%, 34.1%, and 32.7%, respectively. Collectively, these factors contributed a value of 56.6%. The findings highlight the important role of resource access, technology, and education in fostering students' interest in plastic recycling entrepreneurship. These results can inform innovative strategies to promote sustainable entrepreneurship among university students.